2017
DOI: 10.1037/ccp0000224
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and moderation of improvement in cognitive-behavioral and psychodynamic psychotherapy for panic disorder.

Abstract: Objective To identify variables predicting psychotherapy outcome for panic disorder or indicating which of two very different forms of psychotherapy - Panic-Focused Psychodynamic Psychotherapy (PFPP) or Cognitive-Behavioral Therapy (CBT) - would be more effective for particular patients. Method Data were from 161 adults participating in a randomized controlled trial including these psychotherapies. Patients included 104 women; 118 patients were White, 33 were Black, and 10 were of other races; 24 were Latino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…It is, thus, recommended to involve the patients and consider their view on treatment when conducting a treatment plan. This finding is consistent with previous research supporting that patients are more likely to benefit from treatment if they believe in the treatment, and this may strengthen placebo components of treatment (Chambless et al, 2017;Chambless, Tran, & Glass, 1997;Hamilton & Dobson, 2002;Hedman et al, 2012;Wampold, 2015). For clinician's estimation of positive outcome (range 0-10), a rating of 10 was associated with a doubled probability of successful outcome compared to a clinician rating of 5.…”
Section: Discussionsupporting
confidence: 88%
“…It is, thus, recommended to involve the patients and consider their view on treatment when conducting a treatment plan. This finding is consistent with previous research supporting that patients are more likely to benefit from treatment if they believe in the treatment, and this may strengthen placebo components of treatment (Chambless et al, 2017;Chambless, Tran, & Glass, 1997;Hamilton & Dobson, 2002;Hedman et al, 2012;Wampold, 2015). For clinician's estimation of positive outcome (range 0-10), a rating of 10 was associated with a doubled probability of successful outcome compared to a clinician rating of 5.…”
Section: Discussionsupporting
confidence: 88%
“…Increasing emphasis has been put on the impact of treatment related variables on outcome (Brandenburg, 2017;Hedman et al, 2012;Meyer et al, 2002;Simon & Perlis, 2010). Some studies have shown that patients are more likely to benefit from treatment if they believe in the treatment, (Chambless et al, 2017;Chambless, Tran, & Glass, 1997;Hamilton & Dobson, 2002;Hedman et al, 2012;Wampold, 2015) or find the treatment logical (Carter et al, 2011). Research has also shown that adhering to treatment (Hedman et al, 2012) and conducting homework assignments (Mausbach, Moore, Roesch, Cardenas, & Patterson, 2010) are associated with better treatment outcome for both anxiety, depression (Cowan et al, 2008) and insomnia (Harvey, Inglis, & Espie, 2002).…”
Section: Predictors Of Outcomementioning
confidence: 99%
“…Personality problems did also not emerge as a predictor or a moderator. Other studies have also failed to find personality problems (Cluster C) as a predictor of treatment outcome for panic disorder (e.g., Chambless et al, 2017) or anxiety disorders in general (Schneider, Arch, & Wolitzky-Taylor, 2015). However, in a study of patients seeking low-threshold treatment in England (Improved Access to Psychological Therapies), personality problems were associated with worse outcome (Goddard et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have also failed to find personality problems (Cluster C) as a predictor of treatment outcome for panic disorder (e.g., Chambless et al, 2017) or anxiety disorders in general (Schneider, Arch, & Wolitzky-Taylor, 2015). Other studies have also failed to find personality problems (Cluster C) as a predictor of treatment outcome for panic disorder (e.g., Chambless et al, 2017) or anxiety disorders in general (Schneider, Arch, & Wolitzky-Taylor, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation